Significance of fibre length in the clearance of asbestos fibres from the lung. - Morgan, A (1978)
Rats were exposed by inhalation to radioactive anthophyllite asbestos. Animals were then killed serially over a period of 205 days and the fibre content of the lungs measured radiometrically. The lungs were subjected to selective bronchopulmonary lavage and the mean fibre content determined of free cells recovered from the alveolar spaces. The length distributions of fibres recovered from the lungs by lavage, and of those remaining in the lungs following lavage, were measured. Short (less than 5 micrometer) fibres are cleared from the lung via the conducting airways more efficiently than longer fibres and fibres exceeding 50 micrometer in length are not removed from the lungs by this route. Although fibres of about 200 micrometer in length were present in all the lungs examined, the longest which could be recovered by lavage, once fibre deposited in the airways had been cleared, was only about 100 micrometer decreasing to 60-70 micrometer after 205 days. It is suggested that long fibres are more liable than short to penetrate the alveolar wall as they tend to bridge the alveolar ducts and alveoli.